Mathematics in Software Reliability and Quality Assurance - Dohi, Tadashi; Liu, Shaoying (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This monograph concerns the mathematical aspects of software reliability and quality assurance and consists of 11 technical papers in this emerging area. Included are the latest research results related to formal methods and design, automatic software testing, software verification and validation, coalgebra theory, automata theory, hybrid system and software reliability modeling and assessment.